The King and I - Landon, Margaret Dorothea (Mortenson) 1903- .; Lehman, Ernest 1915-.; Rodgers, Richard 1902-.; Hammerstein, Oscar 1895-1960.; Kerr, Deborah 1921-.; Brynner, Yul.; Moreno, Rita.; Lang, Walter; Twentieth Century-Fox Films Corp. ([United States] Twentieth Century-Fox., 1956)
A musical comedy-drama about an English widow who, with her ten-year-old son, goes to Siam in 1862 to educate the King's wives and children in the ways of western culture and subtly influences the King.
Disc 1 (1 hr., 3 min.) -- disc 2 (1 hr., 9 min.)
Music by Richard Rogers and book and lyrics by Oscar Hammerstein II from their musical play based on Anna and the King of Siam by Margaret Landon.
Deborah Kerr, Yul Brynner, Rita Moreno.
Keywords: Leonowens, Anna Harriette (Crawford) -- 1834-1914.; Mongkut -- King of Siam -- 1804-1868.; Musicals